1975
DOI: 10.1073/pnas.72.1.274
|View full text |Cite
|
Sign up to set email alerts
|

Translation and identification of the mRNA species synthesized in vitro by the virion-associated RNA polymerase of vesicular stomatitis virus.

Abstract: Vesicular stomatitis virus messenger RNA has been transcribed in vitro from the viral genome by the virion-associated RNA polymerase in quantities suitable for translation. Wheat germ cell-free extracts programmed with the isolated in vitro 12-18S RNA fraction synthesize polypeptides similar to the viral N, NS, and M proteins, as judged by sodium dodecyl sulfate-polyacrylamide gel electrophoresis and tryptic peptide mapping of the in vitro products and the viral marker polypeptides. In addition, the RNA synthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
44
0

Year Published

1976
1976
2012
2012

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(48 citation statements)
references
References 28 publications
4
44
0
Order By: Relevance
“…Perhaps this protein is a nonglycosylated G protein precursor precipitated with anti-VSV IgG. This result is in agreement with previous data that there was little or no production of virus glycoproteins in cell-free translation systems (4,5,12).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Perhaps this protein is a nonglycosylated G protein precursor precipitated with anti-VSV IgG. This result is in agreement with previous data that there was little or no production of virus glycoproteins in cell-free translation systems (4,5,12).…”
Section: Discussionsupporting
confidence: 92%
“…The translation products were immunopreeipitated and the amount of immunoprecipitable radioactivity [~S~] was counted. B SDS-polyaci3damide gel electrophoresis ofimmunoprecipitable polypeptides from the cellfree systems programmed by RNA fractions (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11) kilodaltons. I t is in correlation with a molecular weight of N P protein (7,10).…”
Section: Discussionmentioning
confidence: 99%
“…This small plaque isolate was shown to be 1,000 times less lethal than wild-type virus in animal models but still able to induce a robust interferon response (39). Further characterization showed that S 2 VSV transcribes more small viral mRNA species (12S to 18S; N, P, M and G mRNA) but less of the largest viral RNA species (40S; replication products) than wild-type VSV (5,12,23,32).For our studies both wild-type VSV-San Juan and S 2 VSV were obtained and plaque purified and the growth attenuation earlier reported was verified. To quantify the observed attenuation, we carried out a time course of infection with wild-type and S 2 VSV and measured the titer of virus released into supernatant fluid by plaque assay on BHK-21 cells.…”
supporting
confidence: 51%
“…This small plaque isolate was shown to be 1,000 times less lethal than wild-type virus in animal models but still able to induce a robust interferon response (39). Further characterization showed that S 2 VSV transcribes more small viral mRNA species (12S to 18S; N, P, M and G mRNA) but less of the largest viral RNA species (40S; replication products) than wild-type VSV (5,12,23,32).…”
mentioning
confidence: 99%
See 1 more Smart Citation